2011
DOI: 10.1002/jwmg.313
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection by grassland snakes at northern range limits: Implications for conservation

Abstract: Animal populations at northern range limits may use habitat differently from those at range cores, requiring distinct conservation plans. Snakes are ectotherms that often have very specific requirements, but few studies have focused on the effect of northern latitudes on habitat selection by grassland snakes. We studied movement and habitat selection of 2 sympatric snake species at their northern range limits on the North American Great Plains: the eastern yellow‐bellied racer (Coluber constrictor flaviventris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(84 citation statements)
references
References 43 publications
8
76
0
Order By: Relevance
“…Though suitable overwintering sites are imperative to the persistence of northern snake populations, small reserves around communal hibernacula have been identified as insufficient to protect snakes during the active season (Martino et al , Williams et al ); our results show that identifying summer grounds will likely require species‐specific considerations. Martino et al () suggested that simply creating management zones around dens alone would likely not be sufficient to include summer grounds for northern snake populations, and they further suggested that this can be mitigated by either defining much larger den zones or identifying a corridor system linking smaller protected areas surrounding winter and summer habitats. Our results show the home ranges of these northern grassland snakes are indeed dumbbell‐shaped, and management considerations must include the den area, corridors, and the summering grounds.…”
Section: Management Implicationsmentioning
confidence: 78%
See 3 more Smart Citations
“…Though suitable overwintering sites are imperative to the persistence of northern snake populations, small reserves around communal hibernacula have been identified as insufficient to protect snakes during the active season (Martino et al , Williams et al ); our results show that identifying summer grounds will likely require species‐specific considerations. Martino et al () suggested that simply creating management zones around dens alone would likely not be sufficient to include summer grounds for northern snake populations, and they further suggested that this can be mitigated by either defining much larger den zones or identifying a corridor system linking smaller protected areas surrounding winter and summer habitats. Our results show the home ranges of these northern grassland snakes are indeed dumbbell‐shaped, and management considerations must include the den area, corridors, and the summering grounds.…”
Section: Management Implicationsmentioning
confidence: 78%
“…Roads were used according to their availability in the environment by racers and rattlesnakes. In contrast, compositional analysis revealed bullsnakes (data from Martino et al ) select for lowland pasture, hills and slopes, and roads, though lowland pasture ( t 15 = 3.434, P = 0.003) and hills and slopes ( t 15 = 4.830, P ≤ 0.001) were used more than roads. All 3 species avoided native upland, crop areas, irrigated areas, and open water, which were used significantly less than the other available landscape types (Table ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…), studies of movement patterns tend to be at relatively large spatial scales (10 2 –10 3 m) that emphasize differential habitat use, mate‐searching patterns, and migration between seasonal foraging‐, mating‐ and/or overwintering‐grounds (Reinert ; Glaudas & Rodríguez‐Robles ; Wastell & Mackessy ; Martino et al. ; Miller et al. ; Pittman et al.…”
Section: Introductionmentioning
confidence: 99%